Finding the Optimum Value-Added Tax Threshold of Small and Medium Businesses in Indonesia - Lungun, Rahadian (Magister Akuntansi Universitas Pancasila, 2025)
Purpose: This study investigates the optimal Value-Added Tax (VAT) registration threshold for small and medium enterprises (SMEs) in Indonesia, aiming to enhance VAT revenue without raising the tax rate. Despite VAT being a significant source of revenue for Indonesia, the current VAT registration threshold of 4.8 billion rupiahs is relatively high compared to other countries, potentially limiting tax revenue from businesses just below this level.Methodology: The study calculates the optimal VAT threshold for various business sectors using the Keen and Mintz model and administrative data from the Directorate General of Taxes.Finding: The results show that the average optimal threshold is lower than the current threshold, with the mining and quarrying sector having the highest threshold at approximately 4.26 billion rupiahs and the accommodation and food service sectors the lowest.Implication: The implication of this study suggests that reducing the VAT threshold could expand the tax base and increase revenue without raising VAT rates.Originality: The study contributes to the ongoing discourse on optimising Indonesia's VAT system and recommends revising the threshold to reflect sector-specific needs better and enhance overall tax efficiency.